Preparation method and application of biomass composite adsorbent
By reacting a specific proportion of sodium lignin sulfate, toluene diisocyanate with carboxymethyl chitosan in the presence of a catalyst, a biomass composite adsorbent with synergistic adsorption effect is solved, and the problems of high cost and insufficient performance of traditional adsorbent materials are achieved, and the adsorption effect of efficient and low-cost organic dyes is supported, supporting environmental protection and sustainable development.
Patent Information
- Application Number
- CN202411940503.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional adsorbent materials such as activated carbon are costly and difficult to regenerate when dealing with organic dye pollution, and may cause secondary pollution to water and the environment, limiting their widespread use. At the same time, carboxymethyl chitosan has low solubility and is prone to agglomeration in an alkaline environment, which limits its adsorption performance.
By reacting a specific proportion of sodium lignin sulfate, toluene diisocyanate with carboxymethyl chitosan in the presence of the catalyst dibutyl tin dilaurate, a biomass composite adsorbent with a synergistic adsorption effect is constructed. This method significantly improves adsorption performance and structural stability through the synergistic effect of hydrogen bonds, ion bonds and π-π stacking effects.
The prepared biomass composite adsorbent has the ability to efficiently adsorb organic dyes, especially the adsorption amount to maraceae green dyes is as high as 188 mg/g, and is inexpensive. It is suitable for the treatment of organic dyes or contaminated wastewater, supporting environmental protection and sustainable development.
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorption materials, and in particular to a preparation method and application of a biomass composite adsorbent. Background Art
[0002] At present, among the many existing technologies for solving the water and environmental pollution problems caused by organic dye discharge, adsorption has attracted much attention due to its simple operation, high efficiency and wide application range. However, traditional adsorption materials such as activated carbon are expensive, difficult to regenerate, and may cause secondary pollution to water and the environment, which limits their wide application.
[0003] In response to the above problems, researchers found that biomass adsorption materials have the advantages of low cost, high efficiency and regeneration. Among them, carboxymethyl chitosan is a low-cost and highly efficient bio-based material. The amino (-NH2) and hydroxyl (-OH) groups on its molecular chain can electrostatically attract organic dyes and form hydrogen bonds to adsorb organic dyes. However, although carboxymethyl chitosan itself has a certain dye adsorption capacity, its low solubility in alkaline environments and easy aggregation in water limit its adsorption performance. Therefore, modifying carboxymethyl chitosan and introducing other functional groups to increase adsorption sites and optimize the adsorption window have become the key to improving its adsorption performance and expanding its application potential. The preparation of high-efficiency adsorbents using carboxymethyl chitosan as raw material can not only effectively solve the problem of water resource pollution, but also increase the added value of carboxymethyl chitosan, promote the application of carboxymethyl chitosan in more fields, and achieve sustainable development of the environment and economy.
[0004] Therefore, the present invention develops a new adsorption material with high-efficiency adsorption performance based on carboxymethyl chitosan, which is of great significance to water resource regeneration, environmental protection and sustainable development. Summary of the invention
[0005] In view of the above deficiencies in the prior art, the present invention provides a preparation method and application of a biomass composite adsorbent with high adsorption performance and low cost, which is of great significance to water resource regeneration, environmental protection and sustainable development.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] In a first aspect, the present invention provides a method for preparing a biomass composite adsorbent, comprising the following steps:
[0008] S1, mixing sodium lignin sulfate and xylene evenly to obtain sodium lignin sulfate slurry, recorded as slurry A; mixing carboxymethyl chitosan and xylene evenly to obtain carboxymethyl chitosan slurry, recorded as slurry B;
[0009] S2. Under the protection of inert gas, the slurry A and the slurry B are evenly mixed, toluene diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 100-110° C. to obtain a biomass composite adsorbent.
[0010] In view of the low solubility and insufficient adsorption performance of carboxymethyl chitosan in alkaline environment, the present invention uses a specific ratio of sodium lignin sulfate, toluene diisocyanate and carboxymethyl chitosan to react in the presence of a catalyst dibutyltin dilaurate, and constructs a biomass composite adsorbent with a synergistic adsorption effect, wherein the amino and hydroxyl groups in carboxymethyl chitosan are key active sites, which can form hydrogen bonds or ionic bonds with polar functional groups (such as carboxyl groups, sulfonic acid groups, etc.) in dye molecules, which not only effectively improves the adsorption performance, but also increases the structural stability of the composite adsorbent material and the density of active sites. Sodium lignin sulfate has a large number of hydroxyl groups, and both it and toluene diisocyanate contain benzene rings, wherein the benzene rings can form non-covalent interactions with the aromatic rings in the dye molecules through the π-π stacking effect, further significantly improving the adsorption capacity and selectivity of the adsorbent material. The present invention successfully composites sodium lignin sulfate with carboxymethyl chitosan through toluene diisocyanate and a catalyst, and the synergistic effect between a large number of amino, hydroxyl, benzene ring and carbonyl groups in the obtained biomass composite adsorbent can significantly optimize the chemical and physical adsorption processes of the adsorbent, making it have the characteristics of high-efficiency adsorption.
[0011] Furthermore, the mass ratio of the sodium lignin sulfate, carboxymethyl chitosan and toluene diisocyanate is (5-20): (5-16): (11-22).
[0012] Furthermore, the mass ratio of the sodium lignin sulfate, carboxymethyl chitosan and toluene diisocyanate is (9-13):(9-11):15.
[0013] Furthermore, the amount of the catalyst used is 5% to 10% of the total mass of sodium lignin sulfate, carboxymethyl chitosan and toluene diisocyanate.
[0014] Furthermore, the mass ratio of sodium lignin sulfate to xylene in slurry A is 15:(35-52).
[0015] Furthermore, the mass ratio of carboxymethyl chitosan to xylene in slurry B is 14:(35-52).
[0016] Furthermore, the mixing method in step S1 is ultrasonic vibration.
[0017] Furthermore, the inert gas in step S2 is nitrogen or argon.
[0018] Furthermore, the reaction time in step S2 is 6 to 8 h.
[0019] Furthermore, the biomass composite adsorbent has an adsorption capacity of up to 188 mg / g for malachite green dye.
[0020] In a second aspect, the present invention provides a biomass composite adsorbent prepared by the method.
[0021] In a third aspect, the present invention provides use of the biomass composite adsorbent in the treatment of organic dyes or polluted wastewater.
[0022] Compared with the prior art, the present invention is beneficial in that:
[0023] (1) In the presence of a catalyst, dibutyltin dilaurate, sodium lignin sulfate and carboxymethyl chitosan are compounded using toluene diisocyanate to construct a biomass-based composite adsorbent with a synergistic adsorption effect. The synergistic effect of a large number of amino, hydroxyl, benzene ring and carbonyl groups in the adsorbent significantly enhances the chemical and physical adsorption process between the adsorbent material and the dye molecules, making it have the characteristics of high-efficiency adsorption.
[0024] (2) Toluene diisocyanate in the present invention plays a key role. Under the cross-linking effect of toluene diisocyanate, carboxymethyl chitosan and sodium lignin sulfate are successfully constructed into a composite material with a rigid macromolecular network. At the same time, the polarized structure of the carbonyl group in toluene diisocyanate enables the adsorbent and the organic dye molecules to be more tightly combined, significantly improving the mechanical strength of the adsorbent material and its dispersibility in water. In addition, toluene diisocyanate causes carboxymethyl chitosan to undergo an open-chain reaction through a nucleophilic reaction, exposing more active sites such as amino groups and hydroxyl groups, further enhancing the adsorption capacity of organic dyes, ensuring that the adsorbent can be evenly dispersed in the aqueous phase, and providing a basic support for achieving efficient adsorption performance.
[0025] (3) The carboxymethyl chitosan and sodium lignin sulfate used in the biomass composite adsorbent provided by the present invention are renewable biomass raw materials, which achieve efficient removal of organic dyes in papermaking wastewater, reduce the production cost of the adsorbent, and provide a new way to recycle waste paper pulp. Through resource recycling and environmentally friendly design, the present invention provides a practical solution for sustainable development and ecological environmental protection, while promoting the efficient development and application of biomass materials, showing important economic and social value.
[0026] (4) The preparation method of the biomass composite adsorbent provided by the present invention is simple and easy to operate, does not involve expensive and dangerous chemicals, is green and environmentally friendly, and is conducive to large-scale production. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The present invention provides a method for preparing a biomass composite adsorbent, comprising the following steps:
[0029] S1. Mix sodium lignin sulfate and xylene by ultrasonic vibration to obtain sodium lignin sulfate slurry, which is recorded as slurry A; mix carboxymethyl chitosan and xylene by ultrasonic vibration to obtain carboxymethyl chitosan slurry, which is recorded as slurry B;
[0030] S2. Under the protection of inert gas, the slurry A and the slurry B are evenly mixed, toluene diisocyanate and dibutyltin dilaurate are added, and after reacting at 100-110° C., the mixture is filtered, washed, dried, ground, and sieved to obtain a biomass composite adsorbent.
[0031] In some examples, the mass ratio of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate is (5-20): (5-16): (11-22).
[0032] In some examples, the amount of the catalyst used is 5% to 10% of the total mass of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate.
[0033] In some examples, the mass ratio of sodium lignin sulfate to xylene in slurry A is 15:(35-52); the mass ratio of carboxymethyl chitosan to xylene in slurry B is 14:(35-52).
[0034] In some examples, the inert gas in step S2 is nitrogen or argon.
[0035] In some examples, the reaction time in step S2 is 6 to 8 hours.
[0036] In some examples, the biomass composite adsorbent has an adsorption capacity of up to 188 mg / g for malachite green dye.
[0037] In the following specific examples, unless otherwise specified, all the raw materials and reagents used were purchased conventionally.
[0038] Example 1
[0039] A biomass composite adsorbent, the preparation steps are as follows:
[0040] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0041] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration to obtain chitosan slurry, which is recorded as slurry B;
[0042] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate 5:16:22, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate, and stirred at a constant speed for 7 h at 105 °C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and sieved through a 200-mesh sieve to obtain a biomass composite adsorbent.
[0043] Example 2
[0044] A biomass composite adsorbent, the preparation steps are as follows:
[0045] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0046] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration to obtain chitosan slurry, which is recorded as slurry B;
[0047] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate 9:14:20, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate, and stirred at a constant speed for 7 h at 105 °C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and sieved through a 200-mesh sieve to obtain a biomass composite adsorbent.
[0048] Example 3
[0049] A biomass composite adsorbent, the preparation steps are as follows:
[0050] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0051] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration to obtain chitosan slurry, which is recorded as slurry B;
[0052] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate 11:10:15, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass composite adsorbent.
[0053] Example 4
[0054] A biomass composite adsorbent, the preparation steps are as follows:
[0055] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0056] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration to obtain chitosan slurry, which is recorded as slurry B;
[0057] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate 15:8:13, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass composite adsorbent.
[0058] Example 5
[0059] A biomass composite adsorbent, the preparation steps are as follows:
[0060] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0061] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration to obtain chitosan slurry, which is recorded as slurry B;
[0062] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate 20:5:11, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass composite adsorbent.
[0063] Comparative Example 1
[0064] A carboxymethyl chitosan adsorbent, the preparation steps are as follows:
[0065] S1. Add carboxymethyl chitosan and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration, which is recorded as slurry A;
[0066] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration is recorded as slurry B;
[0067] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of carboxymethyl chitosan and toluene diisocyanate 21:15, and the amount of dibutyltin dilaurate was 8% of the total mass of carboxymethyl chitosan and toluene diisocyanate, and stirred at a constant speed for 7 h at 105 ° C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 ° C for 12 h, ground and passed through a 200-mesh sieve to obtain a carboxymethyl chitosan adsorbent.
[0068] Comparative Example 2
[0069] A biomass composite adsorbent, the preparation steps are as follows:
[0070] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0071] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration to obtain chitosan slurry, which is recorded as slurry B;
[0072] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then dibutyltin dilaurate was added to make the mass ratio of sodium lignin sulfate and carboxymethyl chitosan 11:10, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate and carboxymethyl chitosan, and stirred at 105 °C for 7 h. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and sieved through a 200-mesh sieve to obtain a biomass composite adsorbent.
[0073] Comparative Example 3
[0074] A sodium sulfate lignin adsorbent, the preparation steps are as follows:
[0075] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration, which is recorded as slurry A;
[0076] S2, adding sodium lignin sulfate and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration is recorded as slurry B;
[0077] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate and toluene diisocyanate 21:15, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate and toluene diisocyanate, and stirred at 105 °C for 7 h. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and passed through a 200-mesh sieve to obtain a sodium lignin sulfate adsorbent.
[0078] Comparative Example 4
[0079] A biomass composite adsorbent, the preparation steps are as follows:
[0080] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0081] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration to obtain chitosan slurry, which is recorded as slurry B;
[0082] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate 3:18:15, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate, and stirred at a constant speed for 7 h at 105 °C. Finally, the mixture was filtered, washed with deionized water for 3 times, dried at 80 °C for 12 h, ground and sieved through a 200-mesh sieve to obtain a biomass composite adsorbent.
[0083] Comparative Example 5
[0084] A biomass composite adsorbent, the preparation steps are as follows:
[0085] S1. Add sodium lignin sulfate and xylene in a mass ratio of 15:43 into a beaker, and disperse and dissolve them by ultrasonic vibration to obtain an alkaline lignin slurry, which is recorded as slurry A;
[0086] S2, adding carboxymethyl chitosan and xylene in a mass ratio of 14:43 into a beaker, and dispersing and dissolving by ultrasonic vibration to obtain chitosan slurry, which is recorded as slurry B;
[0087] S3. Under argon protection, the prepared slurry A and slurry B were mixed evenly, and then toluene diisocyanate and dibutyltin dilaurate were added to make the mass ratio of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate 18:3:15, and the amount of dibutyltin dilaurate was 8% of the total mass of sodium lignin sulfate, carboxymethyl chitosan, and toluene diisocyanate. Stir at a constant speed for 7 h at 105 °C. Finally, filter and wash with deionized water for 3 times, dry at 80 °C for 12 h, grind and pass through a 200-mesh sieve to obtain a biomass composite adsorbent.
[0088] Application Examples
[0089] The analytical reagent malachite green was added to deionized water to prepare 1 L of malachite green solution with an initial concentration of 200 mg / L. Then 20 mg of adsorbent was weighed and added to the malachite green solution. The mixture was stirred at a constant speed at 25 °C for 3 h. The malachite green concentration after adsorption was measured by atomic absorption spectrophotometry, and the adsorption amount was calculated. The test results are shown in Table 1.
[0090] The equilibrium adsorption amount mentioned in the test is the result of the adsorbent reaching equilibrium by oscillating adsorption of a certain concentration of organic dye solution. The concentration of organic dye before and after adsorption is determined by atomic absorption spectrophotometry, and the adsorption amount is calculated as follows:
[0091]
[0092] In the formula, is the equilibrium adsorption capacity, the unit is mg / g, C o is the initial concentration of the organic dye in the solution before adsorption, expressed in mg / L, C e is the equilibrium concentration of the organic dye in the remaining solution after adsorption, recorded in mg / L, m is the mass of the adsorbent, recorded in g, and V is the volume of the organic dye solution, recorded in L.
[0093] Table 1: Test results of malachite green adsorption by adsorbents prepared in Examples 1 to 5 and Comparative Examples 1 to 5
[0094]
[0095] As can be seen from Table 1, the adsorbent prepared in Example 3 has the highest content of malachite green adsorbed, and the adsorbent prepared in Comparative Example 1 has the least content of malachite green adsorbed. Compared with Example 3, Comparative Example 1 uses carboxymethyl chitosan as a raw material, and under the action of toluene diisocyanate and a catalyst, the carboxymethyl chitosan undergoes a cross-linking reaction within or between molecules to obtain a carboxymethyl chitosan adsorbent, and its adsorption amount is much lower than that of the biomass composite adsorbent prepared by the present invention. The reason may be that natural carboxymethyl chitosan only has its own adsorption groups and a small amount of carbonyl and phenyl groups brought by toluene diisocyanate, and its adsorption effect on malachite green is relatively limited; compared with Example 3, toluene diisocyanate is not added in Comparative Example 2, and the carboxymethyl chitosan and lignin sulfate are not cross-linked. There is no cross-linking reaction between sodium, and it is only combined by electrostatic adsorption such as hydrogen bonds, so it cannot effectively improve the dispersion effect of the adsorbent, so that the adsorption amount of the adsorbent in Comparative Example 2 is poor; compared with Example 3, Comparative Example 3 uses sodium lignin sulfate as a raw material, and under the action of toluene diisocyanate and a catalyst, sodium lignin sulfate undergoes a cross-linking reaction within or between molecules to obtain a sodium lignin sulfate adsorbent, and its adsorption amount is much lower than that of the biomass composite adsorbent prepared by the present invention. Although the hydroxyl and benzene ring groups contained in sodium lignin sulfate have a certain adsorption effect on malachite green, the adsorption effect is limited. Compared with Example 3, in Comparative Example 4, sodium lignin sulfate is reduced, and the amount of carboxymethyl chitosan is increased to make the mass ratio 3:18. The adsorption amount of the prepared adsorbent is poorer than that of the adsorbent in the present invention. The reason may be that the very small amount of sodium lignin sulfate leads to a reduction in the adsorption sites provided by sodium lignin sulfate, and a large amount of carboxymethyl chitosan does not participate in the cross-linking reaction. Compared with Example 3, in Comparative Example 5, sodium lignin sulfate was added and the amount of carboxymethyl chitosan was reduced. The reason for the decrease in adsorption amount was the same as that in Comparative Example 4, which was due to the reduction of active sites.
[0096] In summary, in the presence of dibutyltin dilaurate and toluene diisocyanate, a specific ratio of sodium lignin sulfate and carboxymethyl chitosan are used to compound to obtain a biomass composite adsorbent. The method of the present invention is simple to operate and low in cost. The prepared biomass composite adsorbent has excellent dye adsorption capacity, wherein the adsorbent has an adsorption capacity of up to 188 mg / g for malachite green dye, and can be widely used in the treatment of organic dyes or polluted wastewater.
[0097] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for preparing a biomass composite adsorbent, characterized in that: The steps include: S1, mixing sodium lignin sulfate and xylene evenly to obtain sodium lignin sulfate slurry, recorded as slurry A; mixing carboxymethyl chitosan and xylene evenly to obtain carboxymethyl chitosan slurry, recorded as slurry B; S2. Under the protection of inert gas, the slurry A and the slurry B are evenly mixed, toluene diisocyanate and dibutyltin dilaurate are added, and the mixture is reacted at 100-110° C. to obtain a biomass composite adsorbent.
2. The method for preparing a biomass composite adsorbent according to claim 1, characterized in that: The mass ratio of the sodium lignin sulfate, carboxymethyl chitosan and toluene diisocyanate is (5-20): (5-16): (11-22).
3. The method for preparing a biomass composite adsorbent according to claim 2, characterized in that: The mass ratio of the sodium lignin sulfate, carboxymethyl chitosan and toluene diisocyanate is (9-13):(9-11):
15.
4. The method for preparing a biomass composite adsorbent according to claim 1, characterized in that: The mass ratio of sodium lignin sulfate to xylene in slurry A is 15:(35-52).
5. The method for preparing a biomass composite adsorbent according to claim 1, characterized in that: The mass ratio of carboxymethyl chitosan to xylene in slurry B is 14:(35-52).
6. The method for preparing a biomass composite adsorbent according to claim 1, characterized in that: The reaction time in step S2 is 6 to 8 h.
7. The method for preparing a biomass composite adsorbent according to claim 1, characterized in that: The mixing method in step S1 is ultrasonic vibration.
8. The method for preparing a biomass composite adsorbent according to claim 1, characterized in that: The amount of dibutyltin dilaurate used is 5% to 10% of the total mass of sodium lignin sulfate, carboxymethyl chitosan and toluene diisocyanate.
9. The biomass composite adsorbent prepared by the method according to any one of claims 1 to 8.
10. Use of the biomass composite adsorbent as claimed in claim 9 in the treatment of organic dyes or polluted wastewater.